Direction of first bystander call for help is associated with outcome from out-of-hospital cardiac arrest - Nehme, Z.; Andrew, E.; Cameron, P.; Bray, Janet; Meredith, I.; Bernard, S.; Smith, K. (2014)
Background: Preventable bystander delays following out-of-hospital cardiac arrest (OHCA) are common, and include bystanders inappropriately directing their calls for help. Methods: We retrospectively extracted Utstein-style data from the Victorian Ambulance Cardiac Arrest Registry (VACAR) for adult OHCA occurring in Victoria, Australia, between July 2002 and June 2012. Emergency medical service (EMS) witnessed events were excluded. Cases were assigned into two groups on the basis of the first bystander call for help being directed to EMS. Study outcomes were: likelihood of receiving EMS treatment; survival to hospital, and; survival to hospital discharge. Results: A total of 44. 499 adult OHCA cases attended by EMS were identified, of which first bystander calls for help were not directed to EMS in 2842 (6.4%) cases. Calls to a relative, friend or neighbour accounted for almost 60% of the total emergency call delays. Patient characteristics and survival outcomes were consistently less favourable when calls were directed to others. First bystander call to others was independently associated with older age, male gender, arrest in private location, and arrest in a rural region. The risk-adjusted odds of treatment by EMS (OR 1.33, 95% CI 1.20-1.48), survival to hospital (OR 1.64, 95% CI 1.37-1.96) and survival to hospital discharge (OR 1.64, 95% CI 1.13-2.36) were significantly improved if bystanders called EMS first. Conclusion: The frequency of inappropriate bystander calls following OHCA was low, but associated with a reduced likelihood of treatment by EMS and poorer survival outcomes.